First trimester thyroid stimulating hormone as an independent risk factor for adverse pregnancy outcome. (17th September 2017) - Arbib, Nissim; Hadar, Eran; Sneh-Arbib, Orly; Chen, Rony; Wiznitzer, Arnon; Gabbay-Benziv, Rinat
Abstract: Purpose : Maternal thyroid gland dysfunction may adversely affect pregnancy outcome. We aimed to examine the association between subclinical thyroid dysfunction, both hypothyroidism and hyperthyroidism, to adverse pregnancy outcome. Materials and methods : Retrospective cohort study of all women with an available first trimester thyroid function testing and known pregnancy outcome, categorized to subclinical hypothyroidism, or hyperthyroidism and evaluated for complication during gestation and delivery. Results : Four thousand five hundred and four women were included in the final analysis – 3231 were euthyroid, 73 (1.6%) were categorized as subclinical hyperthyroidism and 1200 (26.6%) had subclinical hypothyroidism. Low thyroid-stimulating hormone (TSH) levels, i.e. subclinical hyperthyroidism, correlates with higher rates of placental abruption and extremely low birth weight, below 1500 g. Also, the risk for preterm delivery prior to 34 gestational weeks is higher among women with subclinical hypothyroidism, with greater risk among those with a higher TSH level. (OR 1.81, 95% CI 1.0–3.28 for TSH 2.5–4.0 mIU/L and OR 2.33, 95% CI 1.11–4.42 for those with TSH > 4 4.0 mIU/L). Conclusions : Subclinical hypothyroidism is associated with an increased risk for preterm delivery prior to 34 gestational weeks. Additionally, subclinical hyperthyroidism may also have a role in adverse pregnancy outcome – low birth weight and placental abruption – although this needs to be further explored.